Paraquat Induces Lung Injury via miR-199-Mediated SET in a Mouse Model - Cai, Quan; Jin, Yan; Jia, Ziyi; Liu, Zhi (Frontiers in Pharmacology, 2022)
Objective: To explore the molecular mechanism of lung injury caused by paraquat (PQ) poisoning by investigating miR-199-mediated SET. Methods: A paraquat poisoning model was established in C57BL/6 male mice via intraperitoneal injection of paraquat. The mice were transfected with miR-199 siRNA and or mimic. After 14-day treatment, pathophysiological changes of lung were observed and lung tissue was analyzed via Hematoxylin-Eosin staining. The levels of miR-199, SETs, surfactant protein SP-A and SP-B, inflammatory and oxidative factors were analyzed by qPCR, Western Blot and ELISA kits. Results: A acute lung-injury (ALI) model was established using PQ treatment and confirmed with edema of pulmonary endothelium with low electronic density of endothelial cytoplasm, presence of protein-rich fluid and numerous erythrocytes in alveolar space, concentric figures of damaged tubular myelin, alveolar destruction and increase in inflammatory cell numbers. Compared with the control group, miR-199 and SET levels were reduced in the PQ-treated group. miR-199 siRNA increased the SET level, inflammatory and oxidative levels, and reduced the levels of SP-A and SP-B, and miR-199 mimic reduced the SET level, inflammatory and oxidative levels, and increased the levels of SP-A and SP-B. PQ treatment reduced miR-199 level. Conclusion: Paraquat induces ALI by affecting miR-199-mediated SET.